Olive Leaf Waste Management - Espeso, Julia; Isaza, Alejandro; Lee, Joo Youl; Sörensen, Pia M.; Jurado, Patricia; Avena-Bustillos, Roberto de Jesús; Olaizola, Mikel; Arboleya, Juan Carlos (Frontiers in Sustainable Food Systems, 2021)
Olive trees are the oldest known cultivated trees in the world and present-day cultivation is widespread, with an estimated magnitude of 9 million hectares worldwide. As the olive oil industry has continued to grow, so has the environmental impact of olive oil production, such as the energy and water consumption, gas emissions and waste generation. The largest contributor to waste generation are the olive leaves, an abundant and unavoidable by-product of olive-oil production due to the necessity of tree-pruning. It is estimated that an annual 1.25 million tons of olive leaf waste are generated in Spain alone, around 50% of the total world production. The leaves are currently used for biomass production or animal feed. However, because of their polyphenolic composition, olive leaves have potential in numerous other applications. In this review we analyze the chemical composition of olive leaves, and discuss current processing methods of the olive leaf waste, including thermochemical, biochemical, drying, extraction and condensation methods. We also examine current applications of the treated olive leaves in sectors relating to cattle feed, fertilizers, novel materials, energy generation, and food and pharmaceutical products. The aim of this review is to provide a resource for producers, policy makers, innovators and industry in shaping environmentally sustainable decisions for how olive leaf waste can be utilized and optimized.